The Islamic Republic of Afghanistan : Request for a Three-Year Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for The Islamic Republic of Afghanistan. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses Afghanistan's Request for a Three-Year Arrangement Under the Extended Credit Facility (ECF). The program sets out a structural reform agenda that focuses on institution building, fiscal and financial reforms, and measures to combat corruption to lay the foundations for scaled up private sector development. The envisaged reforms dovetail with Afghanistan's National Development Framework currently being finalized. The program aims to preserve macro-financial stability by implementing prudent fiscal, monetary, and financial policies, and by maintaining external buffers and a flexible exchange rate regime. The IMF staff supports the authorities' request for an ECF arrangement under an IMF-supported program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet